Botulinum toxin in writer's cramp: objective response evaluation in 31 patients. Issue 2 (August 1996) - Wissel, J; Kabus, C; Wenzel, R; Klepsch, S; Schwarz, U; Nebe, A; Schelosky, L; Scholz, U; Poewe, W
Abstract : OBJECTIVES--To quantify the treatment effect of local botulinum toxin injections in writer's cramp a newly developed rating scale of writing performance and a computer assisted analysis of writing speed were used in 31 patients undergoing botulinum toxin therapy. METHODS--Baseline data of the writer's cramp rating scale (WCRS, see appendix) and computer based writing speed analysis were compared with those obtained at the time of subjective best response as recorded during follow up visits. RESULTS--The mean dose injected per session was 133.2 units Dysport divided between two forearm muscles. Of all 124 injection sessions during mean follow up of one year 76% produced a good improvement. The most common side effect was weakness (72% of the follow up visits). The WCRS scores as assessed by a blinded videotape review by four independent raters showed good reliability between raters and a significant improvement after treatment (P < 0.001). The speed of pen movements showed a significant (P < 0.05) increase after treatment at subjective best effect recordings and a significant correlation with WCRS subscores, documenting the validity of the scale. CONCLUSION--The present study is the first to show significant effects of botulinum toxin treatment in patients with writer's cramp on the basis of a quantifiable scale for writing performance which correlates significantly with writing speed measurements. The WCRS as employed in this study might therefore prove a useful rating instrument in other studies assessing severity and treatment response in patients with writer's cramp.